Implementasi Metode Iqro’ Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Anak Usia Dini Di TK Plus Al-Qur’an Darussalam - Ivonne Hafidlatil Kiromi; Intan Sa’adatul Ula (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2023)
This study expects to decide the expansion in ability to peruse of the Qur'an through the iqro strategy in Al-Qur'an In addition to Darussalam Kindergarten. The detailing of the issue in this movement incorporates what the Iqra strategy can mean for understudies' capacity to be great, and through the Iqro technique it is trusted that it can truly change the capacity to peruse the Qur'an rapidly, definitively and accurately. This review utilized  the Study hall Activity Exploration or PTK technique utilizing cycle 1 and cycle 2. From the consequences of the review, the scientist tracked down an expansion in the capacity to peruse the Koran through the Iqra' technique as follows: the classification of understanding the Iqra' strategy was 95% and the classification of perusing Iqra ' easily 90%. This shows that the greater part of the understudies at TK al-Qur'an in addition to Darussalam can peruse the Qur'an smoothly and well